OCEAN BASINS NEAR THE SCOTIA-ANTARCTIC PLATE BOUNDARY: INFLUENCE OF TECTONICS AND PALEOCEANOGRAPHY ON THE CENOZOIC DEPOSITS - Maldonado A.; Bohoyo F.; Lobo F.J.; Rodríguez-Fernández J.; Galindo-Zaldívar J.; Jabaloy A.; Hernández-Molina J.; Suriñach E.; Vázquez J.T. (My University, 2006)
The distribution of seismic units in deposits of the basins near the Antarctic-Scotia plate boundary is described based on the analysis of multichannel seismic reflection profiles. Five main seismic units are identified. The units are bounded by high-amplitude continuous reflectors, named a to d from top to bottom. The two older units are of different age and seismic facies in each basin and were generally deposited during active rifting and seafloor spreading. The three youngest units (3 to 1) exhibit, in contrast, rather similar seismic facies and can be correlated at a regional scale. The deposits are types of contourite drift that resulted from the interplay between the northeastward flow of Weddell Sea Bottom Water (WSBW) and the complex bathymetry in the northern Weddell Sea, and from the influence of the Antarctic Circumpolar Current and the WSBW in the Scotia Sea. A major paleoceanographic event was recorded by Reflector c, during the Middle Miocene, which represents the connection between the Scotia Sea and the Weddell Sea after the opening of Jane Basin. Unit 3 (tentatively dated ~Middle to Late Miocene) shows the initial incursions of the WSBW into the Scotia Sea, which influenced a northward progradational pattern, in contrast to the underlying deposits. The age attributed to Reflector b is coincident with the end of spreading at the West Scotia Ridge (~6.4 Ma). Unit 2 (dated ~Late Miocene to Early Pliocene) includes abundant high-energy, sheeted deposits in the northern Weddell Sea, which may reflect a higher production of WSBW as a result of the advance of the West Antarctic ice-sheet onto the continental shelf. Reflector a represents the last major regional paleoceanographic change. The timing of this event (~3.5-3.8 Ma) coincides with the end of spreading at the Phoenix-Ant-arctic Ridge, but may be also correlated with global events such as initiation of the permanent Northern Hemisphere ice-sheet and a major sea level drop. Unit 1 (dated ~Late Pliocene to Recent) is characterized by abundant chaotic, high-energy sheeted deposits, in addition to a variety of contourites, which suggest intensified deep-water production. Units 1 and 2 show, in addition, a cyclic pattern, more abundant wavy deposits and the development of internal unconformities, all of which attest to alternating periods of increased bottom current energy. © Springer Science+Business Media B.V. 2006.
Keywords: ANTARCTIC CIRCUMPOLAR CURRENT; ANTARCTIC PALAEOCEANOGRAPHY; CONTOURITE DRIFTS; OCEAN BASIN DEVELOPMENT; SEISMIC STRATIGRAPHY; WEDDELL GYRE; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен